(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2025)
Glaucoma is caused by high pressure inside the eye. Glaucoma is the leading cause of irreversible Glaucoma is a group of diseases that damage the optic nerve, the main nerve that leads from the eye to the brain. This damage is usually blindness worldwide. There are two main types of glaucoma: primary open-angle glaucoma and primary angle-closure glaucoma. Early detection and treatment are important to prevent vision loss from glaucoma. There is growing interest in the potential of nutraceuticals for glaucoma management. Nutraceuticals are a class of dietary supplements that are believed to offer health benefits beyond basic nutrition. While they are not a replacement for conventional glaucoma treatment, some nutraceuticals show promise as complementary therapies. Here are some of the nutraceuticals that have been studied in relation to glaucoma: Ginkgo biloba: This herb is one of the most studied nutraceuticals for glaucoma. It has antioxidant and neuroprotective properties, which may help to protect retinal ganglion cells from damage. Some studies have shown that ginkgo biloba may be helpful in slowing the progression of glaucoma, although more research is needed. Coenzyme Q10 (CoQ10): CoQ10 is an antioxidant that is important for mitochondrial function. Mitochondria are the powerhouses of cells, and they are essential for the health of retinal ganglion cells. Studies have shown that CoQ10 may help to improve blood flow to the optic nerve and protect retinal ganglion cells from damage. Magnesium: Magnesium is a mineral that is involved in many important cellular processes, including blood flow regulation and nerve function. Some studies have shown that magnesium may help to lower intraocular pressure (IOP), a major risk factor for glaucoma